Polymer conformation and configuration - Bovey, Frank A. (Frank Alden), 1918-2003 (Current chemical concepts., 1969)
Polymer Conformation and Configuration focuses on the stereochemistry and conformation of vinyl polymers and the application of nuclear magnetic resonance (NMR) spectroscopy to their study and polypeptide conformation by NMR and optical methods. The book first offers information on the configuration of vinyl polymer chains and configurational sequences and the mechanism of vinyl propagation. Discussions focus on the effect of polymerization temperature, polyisopropyl acrylate, polypropylene, Coleman-Fox Propagation Mechanism, and sequence statistics. The text then elaborates on the observati.